Adherence to the 2019 AHA/ACC/HRS Focused Update of the 2014 AHA/ACC/HRS Guideline on the Use of Oral Anticoagulant Agents in Middle Eastern Patients with Atrial Fibrillation: The Jordan Atrial Fibrillation (JoFib) Study - Ayman J. Hammoudeh; Yousef Khader; Nazih Kadri; Eyas Al-Mousa; Yahya Badaineh; Laith Habahbeh; Ramzi Tabbalat; Hesham Janabi; Imad A. Alhaddad (International Journal of Vascular Medicine)
Background. There is a scarcity of studies that evaluate adherence to the utilization of guideline-recommended oral anticoagulant agents (OACs) in patients with atrial fibrillation (AF) in the Middle East. The Jordan Atrial Fibrillation (JoFib) Study evaluated baseline clinical profiles and the utilization of OACs, including vitamin K antagonists (VKAs) and direct OACs (DOACs), in patients with valvular AF (VAF) and nonvalvular AF (NVAF) according to the 2019 focused update of the 2014 AHA/ACC/HRS guidelines. Methods. Consecutive patients with AF were enrolled in 29 hospitals and outpatient clinics. The use of OACs was evaluated in patients with VAF and NVAF according to the prespecified guideline. Results. Of 2000 patients, 177 (8.9%) had VAF and 1823 (91.1%) had NVAF. A VKA was prescribed for 88.1% of the VAF group. In the NVAF group, 1468 (80.5%) of patients had a high CHA2DS2-VASc score, i.e., a score of ≥3 in women and ≥2 in men; 202 (11.1%) patients had an intermediate CHA2DS2-VASc score, i.e., a score of 2 in women and 1 in men; and 153 (8.4%) patients had a low CHA2DS2-VASc score, i.e., a score of 1 in women and 0 in men. Of patients with a high CHA2DS2-VASc score, 1204 (82.0%) received OACs, including DOACs for 784 (53.4%) and VKA for 420 (28.6%) patients. Among patients with an intermediate score, OACs were prescribed for 148 (73.3%) patients, including 107 (53.0%) who received DOACs and 41 (20.3%) patients who received VKA. In patients with a low score, OACs were omitted in 94 (61.4%) patients and prescribed for 59 (38.6%) patients. Multivariate analysis showed that age between 50 and 70 years, CHA2DS2-VASc score of ≥2, a diagnosis of stroke or systemic embolization, and nonparoxysmal AF were significantly associated with increased odds of OAC prescription. Conclusions. The current status of the utilization of OACs in Middle Eastern AF patients appears to be promising and is consistent with the 2019 focused update of the 2014 AHA/ACC/HRS guideline. This trial is registered with NCT03917992.